Transformasi Digital dalam Pendidikan: Telaah Kritis dalam Tinjauan Filosofis - Indah Dwi Lestari; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The digital transformation in education today is positioned as one of the main topics in the global discourse, particularly amidst the Fourth Industrial Revolution. Digital transformation in education, intertwined with the advancements of the Industrial Revolution 4.0, presents numerous ethical dilemmas that not only provoke practical thinking but also stimulate critical analysis from a comprehensive philosophical perspective. This study aims to examine updates on this topic, offering educators' perspectives in addressing digital transformation through a comprehensive approach and an elaboration of expert opinions from a philosophical viewpoint. The research employs a literature study method (library research) by collecting data to understand and analyze theories from various literatures relevant to the title of the study being critically examined. The findings of this study emphasize the necessity for humanization-based learning in the era of digital transformation in education. This approach highlights the role of teachers as facilitators to deliver meaningful learning experiences, integrated with technology that meets the demands and challenges of the times. It also stresses the importance of preserving human values to address ethical dilemmas related to technology and humanity, as well as issues of justice and human welfare.